INDUCTION OF BROWN ADIPOSE TISSUE: A REVIEW - Romauld Sagayaraj, Ivo; S, Akilashree; Devi P, Brindha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Obesity is the major problem which may lead to many other health ailments such as atherosclerosis, stroke, and depression. Both the cause as well as the treatment lies in the adipose tissue. The two main adipocytes, white adipose tissue (WAT) and brown adipose tissue (BAT) are responsible for the accumulation of fat and transformation of fat into heat, respectively. This review discusses the induction of BAT and browning of WAT by different pathways and activators to decrease the rate of obesity. Methods: Understanding the regulators, activators and secreted proteins which induce browning of WAT to BAT, as the BAT engage in thermogenesis process and transform fat into heat rather than storing it (WAT). Some of the core regulators are peroxisome proliferator-activated receptor-Î³, PRDM16, PGC-1Î±. Results: A basic study explained about the origin of BAT and its functions, the function of hormones in BAT growth and its regulations. These studies provided the platform to understand about the mechanism of regulators, activators and secreted proteins which help in treating obesity and its related disorders by inducing the amount of BAT. Conclusion: The major health ailments caused by obesity can be reduced by increasing the activity of BAT and transforming WAT into BAT. A challenging way to treat these ailments is by regulating the activators and hormones responsible for the induction of BAT, so it transforms the excess fat into heat and avoiding the accumulation of fat. By understanding the role of regulators in the adipose tissue can provide various methods to reduce the chance of obesity and enhance efficient treatment in both children and adults.